PENGARUH FIRM SIZE, LEVERAGE DAN SALES GROWTH TERHADAP KINERJA KEUANGAN (Studi keuangan pada sektor property dan real estate yang terdaftar di bursa efek indonesia periode 2017-2021) - Aprianto, Muhammad Shidiq; Norisanti, Nor; Danial, R. Deni Muhammad (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
The research was aimed at obtaining empirical evidence concerning the influence of Firm Size (Ln Total Assets), Leverage (DER) and Sales Growth towards Financial Performance (ROA). The population of data in the research consisted of Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX) for the period of 2017-2021, acquired from the website www.idx.co.id. The research was conducted with a total research sample of 14 companies, a total sample of 70, and a population of 79 Property and Real Estate companies. SPSS software was used for processing research data. Based on the results of F-test, it can be concluded that F-count ≥ F-table, namely 5.221 ≥ 2.85, with significance level of (0.003 <0.05), meaning that there is a significant influence of Firm Size (Ln), Leverage (DER), and Sales Growth (SG) towards Financial Performance (ROA).